2013
DOI: 10.5603/cj.2013.0071
|View full text |Cite
|
Sign up to set email alerts
|

The value of serum osteoprotegerin levels in patients with angina like chest pain undergoing diagnostic coronary angiography

Abstract: (Cardiol J 2013; 20, 3: 261-267)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…The number of identified adipokines is permanently increasing, as well as their potential clinical diagnostic and prognostic value. These adipokines include mainly adiponectin [2-5], leptin [5], tumor necrosis factor (TNF) alpha [6,7], osteoprotegerin [8] interleukin 6 (IL-6) [9], resistin [10], interleukin 1 (IL-1) [11,12], apelin [13], visfatin [14], monocyte chemotactic protein-1 (MCP-1) [15,16], plasminogen activator inhibitor-1 (PAI-1) [17], retinol binding protein 4 (RBP4) [18] and several others.…”
Section: Introductionmentioning
confidence: 99%
“…The number of identified adipokines is permanently increasing, as well as their potential clinical diagnostic and prognostic value. These adipokines include mainly adiponectin [2-5], leptin [5], tumor necrosis factor (TNF) alpha [6,7], osteoprotegerin [8] interleukin 6 (IL-6) [9], resistin [10], interleukin 1 (IL-1) [11,12], apelin [13], visfatin [14], monocyte chemotactic protein-1 (MCP-1) [15,16], plasminogen activator inhibitor-1 (PAI-1) [17], retinol binding protein 4 (RBP4) [18] and several others.…”
Section: Introductionmentioning
confidence: 99%
“…Serum OPG levels increased with the number of lesions on coronary angiography in 200 patients with CAD [ 11 ]. More recently, serum OPG levels correlated with CAD severity by angiographic Gensini score, and CV mortality was higher at midterm follow-up in patients with high OPG levels [ 25 ]. In our study, we further showed a strong association between the degree of complexity of the coronary lesions by SYNTAX score and the OPG level in patients with acute MI.…”
Section: Discussionmentioning
confidence: 99%
“…Relationship between osteoprotegerin levels and stable coronary artery disease: Several studies have shown that OPG levels are predictive of CAD ( 11 , 12 , 42 , 43 ). Lieb et al ( 11 ) measured OPG levels in 3.250 Framingham Heart Study participants and found a positive association between circulating OPG levels (but not RANK-L) and CVD incidence and mortality.…”
Section: Osteoprotegerin: Structure Function and Metabolismmentioning
confidence: 99%
“…Some investigators have demonstrated a positive correlation between circulating OPG levels and the severity of atherosclerosis and the number of diseased vessels, especially in patients with type 2 DM ( 12 , 26 , 42 ). Ghaffari et al ( 43 ) reported a significant relationship between serum OPG levels and coronary artery stenosis. Furthermore, they found that major adverse cardiovascular events occurred more often in patients with higher baseline OPG levels.…”
Section: Osteoprotegerin: Structure Function and Metabolismmentioning
confidence: 99%